Students satisfaction of using E-hailing in UiTM Puncak Alam, Selangor, Malaysia / Sarinah Sabar ... [et al.] - Sabar, Sarinah; Dzulkalnine, Natasha; Syed Ahmad, Sharifah Fazirah; Ahmad, Mohamad Fahimi (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
E-hailing is a transportation service that allows passengers to book a ride through a digital platform or mobile application instead of hailing a taxi or car on the street. The services connect passengers with drivers of private vehicles, often through a network of independent contractors. Key companies providing e-hailing services around the world include Grab, Uber, Maxim and others. Many says that ehailing has disrupted the traditional taxi industry by offering more convenience, pricing transparency, and even offer a higher level of service through driver and vehicle ratings. These services have become an integral part of modern urban transportation, providing an alternative to traditional taxis and public transportation. Providers of e-hailing work hard to keep customers satisfied and loyal to their platforms through a combination of strategies and features designed to enhance the overall customer satisfaction. This study aims to investigate the roles of accessibility, safety, comfortability and price on customers’ satisfaction on e-hailing services, and proposes some suggestions to improve the services. This research espoused a quantitative research methodology by using a survey approach. Data was collected from 108 retail management students of the Faculty of Business and Management, Puncak Alam Campus, Selangor Malaysia. The data were analysed using the Statistical Package of Social Sciences (SPSS). The analyses carried out inclusive of descriptive analysis and cross tabulation analysis. The results show the four variables have roles on students’ satisfaction. This study also determines to provide several solution factors about some e-hailing issues faced by the students. This finding will provide the solutions on how e-hailing needs to improve their services to satisfy students in UiTM Puncak Alam Campus, Selangor Malaysia.